Activation and repression of transcription by auxin-response factors - Ulmasov, Tim (The National Academy of Sciences, 1999)
Auxin-response factors (ARFs) bind with specificity to TGTCTC auxin-response elements (AuxREs), which are found in promoters of primary/early auxin-response genes. Nine different ARFs have been analyzed for their capacity to activate or repress transcription in transient expression assays employing auxin-responsive GUS reporter genes. One ARF appears to act as a repressor. Four ARFs function as activators and contain glutamine-rich activation domains. To achieve transcriptional activation on TGTCTC AuxREs in transient expression assays, ARFs require a conserved dimerization domain found in both ARF and Aux/IAA proteins, but they do not absolutely require their DNA-binding domains. Our results suggest that ARFs can activate or repress transcription by binding to AuxREs directly and that selected ARFs, when overexpressed, may potentiate activation further by associating with an endogenous transcription factor(s) (e.g., an ARF) that is bound to AuxREs. Transfection experiments suggest that TGTCTC AuxREs are occupied regardless of the auxin status in cells and that these occupied AuxREs are activated when exogenous auxin is applied to cells or when ARF activators are overexpressed. The results provide new insight into mechanisms involved with auxin regulation of primary/early-response genes.